A systematic review on the latest developments in testosterone therapy: Innovations, advances, and paradigm shifts. Issue 3 (3rd July 2021) - Al-Zoubi, Raed M.; Yassin, Aksam A.; Alwani, Mustafa; Al-Qudimat, Ahmad; Aboumarzouk, Omar M.; Zarour, Ahmad; Al Ansari, Abdulla
ABSTRACT: Objectives: To review the latest innovations and advances in testosterone treatments including their advantages and disadvantages and to address important issues in testosterone therapy (TTh). Methods: This review was conducted according to the Preferred Reporting Items for Systemic Reviews and Meta-analyses guidelines. The PubMed, MEDLINE, Scopus and Cochrane databases were searched using specifically related key words. The identiﬁed studies were screened for inclusion criteria that included studies discussing one of the four objectives of the systematic review: 1) cut–oﬀ references, 2) prevention/remission of type II diabetes mellitus (T2DM), 3) duration of treatment, and 4) prostate, lower urinary tract symptoms, prostate health, or cancer. The search was limited to the past 15 years. Any studies were not written in English were excluded. Results: The initial literature search retrieved 393 studies. After screening four studies were removed due to duplication, 360 studies were further excluded after reviewing the title, abstract or the whole manuscript due to diﬀerent exclusion criteria or being not focussed on the objective. Finally, 29 studies were included in the review. One study discussed the cut–oﬀ value, four studies discussed the eﬀect of testosterone replacement therapy (TRT) on the control of T2DM, four studies on duration of TRT, and 20 studies discussed the eﬀects of TRT on the prostate Conclusions: Numerous studies have demonstrated the beneﬁts of TTh in overtly hypogonadal men. There are several possible administration routes for testosterone treatment. Each approach has advantages and disadvantages, and the choice of the method of TRT will often be determined by patient preference or co-medication (no intramuscular injections in patients under coumarin or similar anticoagulants). Although new developments are promising, it seems that among the available treatments, only transdermal gel delivery and long-acting injectable testosterone undecanoate provide pharmacokinetic behaviour that gives a steady state level within a physiological range.